Efficient virus-mediated genome editing in cotton using the CRISPR/Cas9 system - Lei, Jianfeng; Li, Yue; Dai, Peihong; Liu, Chao; Zhao, Yi; You, Yangzi; Qu, Yanying; Chen, Quanjia; Liu, Xiaodong (Frontiers in Plant Science, 2022)
Plant virus-mediated sgRNA delivery and expression have great advantages over traditional transformation of intact editing vectors for gene editing because sgRNA expression can rapidly expand and accumulate along with virus replication and movement, resulting in efficient gene editing efficiency. To establish a plant virus-induced genome editing (VIGE) system in cotton, in this study, a VIGE system based on cotton leaf crumple virus (CLCrV) was established in cotton using cotton overexpressing Cas9 (Cas9-OE) as the VIGE receptor. In this system, CLCrV-mediated VIGE could not only target and knock out the cotton GhMAPKKK2, GhCLA1 and GhPDS gene subgroup A and D genome sequences but also achieve double mutation of GhCLA1 and GhPDS genes at the same time, which verified the effectiveness and efficiency of this system. In addition, the off-target effect assay demonstrated that the CLCrV-mediated VIGE system not only has high gene editing efficiency but also high gene editing specificity in cotton. We further explored whether the FT-sgRNA strategy could transport sgRNA to cotton apical meristem (SAM) over long distances to avoid the process of tissue culture to obtain stable genetic cotton mutants. The results showed that the sgRNA fused with FT mRNA at the 5' end could also efficiently achieve targeted editing of endogenous genes in cotton, but it was difficult to detect heritable mutant progeny. The above results showed that the CLCrV-mediated VIGE system provided an accurate and rapid validation tool for screening effective sgRNAs in cotton.